Cosine Modulated and Offset QAM Filter Bank Multicarrier Techniques: A Continuous-Time Prospect. (8th February 2010) - Farhang-Boroujeny Farhang-Boroujeny, Behrouz Behrouz; (George) Yuen (George) Yuen, Chung Him Chung Him
Abstract : Prior to the discovery of the celebrated orthogonal frequency division multiplexing (OFDM), multicarrier techniques that use analog filter banks were introduced in the 1960s. Moreover, advancements in the design of perfect reconstruction filter banks have led to a number developments in the design of prototype digital filters and polyphase structures for efficient implementations of the filter bank multicarrier (FBMC) systems. The main thrust of this paper is to present a tutorial review of the classical works on FBMC systems and show that some of the more recent developments are, in fact, reinventions of multicarrier techniques that have been developed prior of the era of OFDM. We also review the recent novel developments in the design of FBMC systems that are tuned to cope with fast fading wireless channels.